Evaluation of acid resistance in concrete Admixed with silica fume and M-sand (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The M40 grade conventional concrete is made and its response towards acid resistance is compared with concrete partially modified with mineral admixtures and manufactured sand. 5% by weight of binder is replaced with silica fume. Fine aggregate is replaced partially with range of 0%, 15%, 25%, 35% and 45% by manufactured sand. All the mixes are cured under water for 28 days and also cured in two acidic mediums. Acid attack on concrete is studied for HCl and H2SO4 solution with concentration of 1%. All the mixes are observed for its loss in weight and compressive strength after acid attack. The mix with 45% manufactured sand and 5% silica fume showed better performance. There was reduction in loss of weight when manufactured sand is replaced for 45%. Addition of silica fume enhances pozzolanic action at early age and hence early strength of concrete. Modified Concrete resists HCl than H2SO4 solution.